A transitividade em textos da propaganda política eleitoral gratuita televisionada: uma abordagem funcional - DUARTE, Raimunda Dias (Universidade Federal do Pará, 2012)
This study analyses fifty speeches produced for television during Horário Político Eleitoral Gratuito (HPEG) of the elections of 2002 in the state of Pará. The theoretical background lays on the Systemic-Functional Grammar of Halliday (1994) and the study about the Communicative Style of the HPEG of Albuquerque (1999). The research investigates the lexico-grammatical choices made in the transitivity system to uncover how the speaker´s world experiences are construed in the texts produced. It also investigates how the kinds of messages of the Communicative Style of the HPEG are expressed in the texts. The results show that Material and Relational processes are the two main processes most used by politicians. These choices are used as persuasive strategies as they express what the candidate has done and/or will do in case he is elected. They also tell the community that the candidate has the qualities and abilities desired in a politician.